Imitation stone reactive powder concrete

By replacing quartz sand with stone powder and adjusting its particle size grading, the problems of high energy consumption and high cost in the preparation of active powder concrete are solved, and a more environmentally friendly and economical high-strength concrete preparation is achieved.

CN119707394APending Publication Date: 2025-03-28JILIN JIANZHU UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411898523.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

During the preparation process of existing active powder concrete, quartz sand is needed as aggregate, resulting in high energy consumption and high production costs, while also causing pollution to the environment.

Method used

Stone powder is used instead of quartz sand as aggregate for active powder concrete. By adjusting the particle size grading of the stone powder, the strength and compactness of the concrete are improved.

Benefits of technology

It reduces the preparation cost of reactive powder concrete, reduces the pollution to the environment, and improves the strength and application breadth of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005202501000000121
    Figure BDA0005202501000000121
  • Figure BDA0005202501000000131
    Figure BDA0005202501000000131
  • Figure BDA0005202501000000132
    Figure BDA0005202501000000132
Patent Text Reader

Abstract

The invention discloses stone-like reactive powder concrete, and belongs to the technical field of concrete preparation. The stone-like reactive powder concrete is prepared from the following raw materials in parts by mass: 910 to 1015 parts of cement, 280 parts of silica fume, 105 to 210 parts of mineral powder, 238 to 266 parts of water, 7 to 11 parts of water reducing agent, 234 parts of steel fiber and 1167 parts of stone powder, and the water-binder ratio of the stone-like active powder concrete is 0.17-0.19. According to the invention, the stone powder with low quality, low price and different particle sizes is used as the active powder concrete aggregate (completely replacing quartz sand), so that the problem that the active powder concrete in the prior art needs to adopt natural high-quality quartz sand as the aggregate is solved, the manufacturing cost is reduced, and the economic benefit and the environmental benefit are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete preparation, in particular to a stone-like active powder concrete. Background Art

[0002] With the development of society, ordinary concrete is not enough to meet the needs of engineering projects, and a large number of high-performance concrete materials have emerged. Among them, reactive powder concrete (RPC for short), with its high strength, high durability and high toughness, has been continuously used in engineering fields such as bridges, tunnels, airports, nuclear power plants, etc., and scientific researchers are doing more and more research on reactive powder concrete.

[0003] Reactive powder concrete achieves high strength by adding ultrafine mineral particles and controlling the concrete mix ratio and curing time. The strength of active powder concrete is much higher than that of ordinary concrete. High-performance ultrafine mineral powders are added to active powder concrete. These powders can fill the pore structure of concrete, reduce the number and size of infiltration channels, and thus improve the concrete's impermeability. Reactive powder concrete generally uses quartz powder (aggregate) to stabilize the strength of RPC, but the mining of quartz powder will cause environmental pollution and is not conducive to environmental protection.

[0004] As a kind of concrete aggregate, quartz sand needs a lot of grinding process in the process of preparing concrete aggregate, which leads to high energy consumption and high production cost. Therefore, it is urgent to find an aggregate that can replace quartz sand to reduce the preparation cost of reactive powder concrete. Summary of the invention

[0005] The purpose of the present invention is to provide a stone-like active powder concrete to solve the problems existing in the above-mentioned prior art.

[0006] To achieve the above object, the present invention provides the following solutions:

[0007] One of the technical solutions of the present invention: a stone-like active powder concrete, comprising the following raw materials in parts by weight: 910-1015 parts of cement, 280 parts of silica fume, 105-210 parts of mineral powder, 238-266 parts of water, 7-11 parts of water reducing agent, 234 parts of steel fiber and 1167 parts of stone powder;

[0008] The water-to-binder ratio of the stone-like active powder concrete is 0.17-0.19.

[0009] Furthermore, the particle size distribution of the stone powder is as follows:

[0010] 1.18mm≤particle size<4.75mm accounts for 30wt.%;

[0011] The proportion of particles with a diameter of 0.3 mm or less and a diameter of 1.18 mm is 45 wt.%;

[0012] The proportion of particles with a diameter of 0.075 mm or less and less than 0.3 mm is 15 wt.%;

[0013] The proportion of particles with a diameter of less than 0.075 mm is 10 wt.%.

[0014] Aggregate particle size gradation curve is an important factor affecting concrete strength. Using 30% stone powder in the particle size range of 4.75mm to 1.18mm can effectively improve the compression performance of concrete, and can act as concrete rigidity and skeleton, thereby improving the strength of stone-like active powder concrete. Using 45% stone powder in the particle size range of 1.18mm to 0.3mm can relatively reduce the self-shrinkage of active powder concrete due to its small particle size. Using 15% stone powder in the particle size range of 0.3mm to 0.075mm can effectively fill the internal voids of concrete caused by various reasons, making the interior of the concrete denser. Stone powder with a particle size less than 0.075mm can promote the end time of the hydration induction period and acceleration period of cement concrete in advance, and has an enhancing effect on cement hydration. Under the synergistic effect of the above-mentioned stone powder particle sizes, the technical effect of preparing excellent performance stone-like active powder concrete is achieved.

[0015] The present invention uses stone powder instead of quartz sand, which can reduce the production requirements for high-strength concrete (stone powder does not need to be mined or removed, which is more economical and environmentally friendly), reduce economic costs, reduce damage to the environment, and enable high-strength concrete to be widely promoted and applied.

[0016] Furthermore, the mineral powder is S95 grade mineral powder with a specific surface area of ​​≥400kg / m 2 , 7d activity index>75%, 28d activity index>95%, particle size is 0.045mm.

[0017] The main raw material of S95 grade mineral powder is slag, and its chemical composition is active substances such as calcium oxide, silicon dioxide, aluminum oxide, and iron oxide. It has a large specific surface area and a small particle size. When added to concrete, it can play a micro-aggregate effect, fill the gaps in cement mortar, make the concrete denser, and produce a volcanic ash effect. It can react with calcium hydroxide to form CSH gel, which can reduce the hydration heat generated by the hydration reaction of silica fume and cement. Increasing the amount of mineral powder added or increasing the specific surface area of ​​the mineral powder will reduce the porosity of the mortar and improve the mechanical strength.

[0018] By using S95 grade mineral powder to replace the commonly used dark-colored and expensive fly ash, we can obtain concrete with a more beautiful color while ensuring the performance of the concrete.

[0019] Furthermore, the cement is P.Ⅱ52.5 cement with a specific surface area of ​​≥300kg / m 2, loss on ignition ≤3.5%, particle size is 0.04mm.

[0020] P.Ⅱ52.5 cement has the characteristics of high compressive strength, early setting time, strong plasticity, good wear resistance and good workability.

[0021] The silica fume has a silicon dioxide content of >90%, a loss on ignition of <2%, and a particle size of 0.15 μm.

[0022] Silica fume powder is finer, has a smaller molecular structure, an average diameter of 0.15 μm, and a surface area of ​​20 m 2 / g, its particle diameter is only one hundredth of the cement particle diameter, which can accelerate the reaction of cement molecules and fill the molecular pores in cement, thereby maximizing its density. In addition, silica fume has high activity and can improve the early strength of concrete. Adding silica fume can cause a volcanic ash reaction, so that Ca(OH)2 in cement is absorbed in large quantities, forming a CSH gel with a low calcium-silicon ratio. Such CSH gel has a strong ability to absorb alkali, thereby reducing the alkali equivalent in cement mortar, alleviating the alkali erosion of active aggregates, and inhibiting the expansion caused by alkali-silica reaction, thereby achieving the effect of inhibiting alkali-aggregate reaction.

[0023] The steel fiber is a copper-plated steel fiber with a diameter of 0.2 mm, a length of 12 mm, and a tensile strength of ≥2400 MPa.

[0024] The addition of steel fibers makes concrete more resistant to bending and tension, cracking and impact toughness than ordinary concrete. The addition of steel fibers will form a fiber mesh skeleton inside the concrete. The bridging effect of the fibers can inhibit the generation of micro cracks. When the concrete is damaged, the concrete matrix will basically not suffer from brittle failure, but form vertical multiple cracks.

[0025] The water reducer comprises a polycarboxylate water reducer; the water reduction rate of the polycarboxylate water reducer is ≥25%, the air content is ≤6.0%, and the chloride ion content is ≤0.1%.

[0026] The present invention utilizes stone powder to completely replace quartz sand to prepare imitation stone active powder concrete, which can not only reduce the preparation cost of imitation stone active powder concrete, but also greatly reduce the pollution caused to the environment, and can better promote the application of imitation stone active powder concrete. Mineral powder has high activity and plays a reinforcing role in concrete, especially in the middle and late reactions, which helps to improve the late strength of concrete. Moreover, its color is lighter, unlike fly ash which has a darker color, and can be well used in the preparation of imitation stone active powder concrete. Steel fiber can effectively prevent micro cracks from appearing inside concrete, and can delay the development of concrete cracks, and can significantly improve the compressive strength, splitting tensile strength and flexural strength of concrete.

[0027] The second technical solution of the present invention is a method for preparing the above-mentioned stone-like active powder concrete, comprising the following steps:

[0028] After cement, silica fume and mineral powder are mixed evenly, water is added and mixed evenly, then a water reducer is added and mixed evenly, stone powder is added and mixed evenly, and finally steel fiber is added and mixed evenly, and cast to obtain the imitation stone active powder concrete.

[0029] The third technical solution of the present invention: an application of the above-mentioned stone-imitation active powder concrete in the preparation of bridge piers.

[0030] The present invention discloses the following technical effects:

[0031] (1) The present invention utilizes low-quality, low-price, and different-size stone powder as the aggregate of active powder concrete (completely replacing quartz sand), thereby improving the problem that the active powder concrete in the prior art needs to use natural high-quality quartz sand as the aggregate, reducing the production cost and improving the economic and environmental benefits.

[0032] (2) The present invention uses stone powder instead of quartz sand to improve the appearance and color of active powder concrete.

[0033] (3) The active powder concrete prepared by the present invention using stone powder instead of quartz sand has excellent mechanical properties and can be widely used in the construction field that requires high-strength concrete structures.

[0034] (4) The present invention provides technical support for the promotion and application of reactive powder concrete. DETAILED DESCRIPTION

[0035] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0036] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0038] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0039] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0040] The cement used in the specific implementation of the present invention is P.Ⅱ52.5 cement, with a specific surface area of ​​≥300kg / m 2 , loss on ignition ≤3.5%, particle size is 0.04mm.

[0041] The silica fume used in the specific implementation of the present invention has a silicon dioxide content of >90%, a loss on ignition of <2%, and a particle size of 0.15 μm.

[0042] The mineral powder used in the specific embodiment of the present invention is S95 grade mineral powder with a specific surface area of ​​≥400kg / m 2 , 7d activity index>75%, 28d activity index>95%, particle size is 0.045mm.

[0043] The steel fiber used in the specific implementation of the present invention is a copper-plated steel fiber with a diameter of 0.2 mm, a length of 12 mm, and a tensile strength of ≥2400 MPa.

[0044] The water reducing agent used in the specific implementation of the present invention is a polycarboxylate water reducing agent, with a water reduction rate of ≥25%, an air content of ≤6.0%, and a chloride ion content of ≤0.1%.

[0045] The particle size distribution of the stone powder used in the specific implementation of the present invention is as follows:

[0046] 1.18mm≤particle size<4.75mm accounts for 30wt.%;

[0047] The proportion of particles with a diameter of 0.3 mm or less and a diameter of 1.18 mm is 45 wt.%;

[0048] The proportion of particles with a diameter of 0.075 mm or less and less than 0.3 mm is 15 wt.%;

[0049] The proportion of particles with a diameter of less than 0.075 mm is 10 wt.%.

[0050] Example 1

[0051] A stone-like active powder concrete:

[0052] The imitation stone active powder concrete is composed of the following raw materials in parts by mass: 1015kg cement, 280kg silica fume, 105kg mineral powder, 252kg water, 8kg polycarboxylate water reducer, 234kg steel fiber and 1167kg stone powder.

[0053] The preparation method is as follows:

[0054] (1) Cement, silica fume and mineral powder are stirred and mixed to obtain a dry mixture.

[0055] (2) Add water to the dry mixture and stir to obtain cement paste, then add polycarboxylate water reducer to the cement paste, continue stirring, then add stone powder, stir and mix to obtain cement mortar.

[0056] (3) adding steel fibers into cement mortar and continuing to stir, and then pouring and molding after the stirring is completed to obtain stone-like active powder concrete.

[0057] Example 2

[0058] A kind of stone-like active powder concrete (without mineral powder):

[0059] The imitation stone active powder concrete is composed of the following raw materials in parts by mass: 1120kg cement, 280kg silica fume, 224kg water, 4kg polycarboxylate water reducer, 234kg steel fiber and 1167kg stone powder.

[0060] The preparation method is as follows:

[0061] (1) Cement and silica fume are stirred and mixed to obtain a dry mixture.

[0062] (2) Add water to the dry mixture and stir to obtain cement paste, then add polycarboxylate water reducer to the cement paste, continue stirring, then add stone powder, stir and mix to obtain cement mortar.

[0063] (3) adding steel fibers into cement mortar and continuing to stir, and then pouring and molding after the stirring is completed to obtain stone-like active powder concrete.

[0064] Example 3

[0065] A stone-like active powder concrete:

[0066] The imitation stone active powder concrete is composed of the following raw materials in parts by mass: 1015kg cement, 280kg silica fume, 105kg mineral powder, 224kg water, 5kg polycarboxylate water reducer, 234kg steel fiber and 1167kg stone powder.

[0067] The preparation method is the same as Example 1.

[0068] Example 4

[0069] A stone-like active powder concrete:

[0070] The imitation stone active powder concrete is composed of the following raw materials in parts by mass: 910 kg of cement, 280 kg of silica fume, 210 kg of mineral powder, 224 kg of water, 6 kg of polycarboxylate water reducer, 234 kg of steel fiber and 1167 kg of stone powder.

[0071] The preparation method is the same as Example 1.

[0072] Example 5

[0073] A kind of stone-like active powder concrete (without mineral powder):

[0074] The imitation stone active powder concrete is composed of the following raw materials in parts by mass: 1120kg cement, 280kg silica fume, 238kg water, 6kg polycarboxylate water reducer, 234kg steel fiber and 1167kg stone powder.

[0075] The preparation method is as follows:

[0076] (1) Cement and silica fume are stirred and mixed to obtain a dry mixture.

[0077] (2) Add water to the dry mixture and stir to obtain cement paste, then add polycarboxylate water reducer to the cement paste, continue stirring, then add stone powder, stir and mix to obtain cement mortar.

[0078] (3) adding steel fibers into cement mortar and continuing to stir, and then pouring and molding after the stirring is completed to obtain stone-like active powder concrete.

[0079] Example 6

[0080] A stone-like active powder concrete:

[0081] The imitation stone active powder concrete is composed of the following raw materials in parts by mass: 1015kg cement, 280kg silica fume, 105kg mineral powder, 238kg water, 7kg polycarboxylate water reducer, 234kg steel fiber and 1167kg stone powder.

[0082] The preparation method is the same as Example 1.

[0083] Example 7

[0084] A stone-like active powder concrete:

[0085] The imitation stone active powder concrete is composed of the following raw materials in parts by mass: 910 kg of cement, 280 kg of silica fume, 210 kg of mineral powder, 238 kg of water, 8 kg of polycarboxylate water reducer, 234 kg of steel fiber and 1167 kg of stone powder.

[0086] The preparation method is the same as Example 1.

[0087] Example 8

[0088] A kind of stone-like active powder concrete (without mineral powder):

[0089] The imitation stone active powder concrete is composed of the following raw materials in parts by mass: 1120kg cement, 280kg silica fume, 252kg water, 8kg polycarboxylate water reducer, 234kg steel fiber and 1167kg stone powder.

[0090] (1) Cement and silica fume are stirred and mixed to obtain a dry mixture.

[0091] (2) Add water to the dry mixture and stir to obtain cement paste, then add polycarboxylate water reducer to the cement paste, continue stirring, then add stone powder, stir and mix to obtain cement mortar.

[0092] (3) adding steel fibers into cement mortar and continuing to stir, and then pouring and molding after the stirring is completed to obtain stone-like active powder concrete.

[0093] Example 9

[0094] A stone-like active powder concrete:

[0095] The imitation stone active powder concrete is composed of the following raw materials in parts by mass: 910 kg of cement, 280 kg of silica fume, 210 kg of mineral powder, 252 kg of water, 9 kg of polycarboxylate water reducer, 234 kg of steel fiber and 1167 kg of stone powder.

[0096] The preparation method is the same as Example 1.

[0097] Example 10

[0098] A kind of stone-like active powder concrete (without mineral powder):

[0099] The imitation stone active powder concrete is composed of the following raw materials in parts by mass: 1120kg cement, 280kg silica fume, 266kg water, 9kg polycarboxylate water reducer, 234kg steel fiber and 1167kg stone powder.

[0100] The preparation method is as follows:

[0101] (1) Cement and silica fume are stirred and mixed to obtain a dry mixture.

[0102] (2) Add water to the dry mixture and stir to obtain cement paste, then add polycarboxylate water reducer to the cement paste, continue stirring, then add stone powder, stir and mix to obtain cement mortar.

[0103] (3) adding steel fibers into cement mortar and continuing to stir, and then pouring and molding after the stirring is completed to obtain stone-like active powder concrete.

[0104] Embodiment 11

[0105] A stone-like active powder concrete:

[0106] The imitation stone active powder concrete is composed of the following raw materials in parts by mass: 1015kg cement, 280kg silica fume, 105kg mineral powder, 266kg water, 10kg polycarboxylate water reducer, 234kg steel fiber and 1167kg stone powder.

[0107] The preparation method is the same as Example 1.

[0108] Example 12

[0109] A stone-like active powder concrete:

[0110] The imitation stone active powder concrete is composed of the following raw materials in parts by mass: 910 kg of cement, 280 kg of silica fume, 210 kg of mineral powder, 266 kg of water, 11 kg of polycarboxylic acid water reducer, 234 kg of steel fiber and 1167 kg of stone powder.

[0111] The preparation method is the same as Example 1.

[0112] Example 13

[0113] A kind of stone-like active powder concrete (without mineral powder):

[0114] The imitation stone active powder concrete is composed of the following raw materials in parts by mass: 1120kg cement, 280kg silica fume, 280kg water, 11kg polycarboxylate water reducer, 234kg steel fiber and 1167kg stone powder.

[0115] The preparation method is as follows:

[0116] (1) Cement and silica fume are stirred and mixed to obtain a dry mixture.

[0117] (2) Add water to the dry mixture and stir to obtain cement paste, then add polycarboxylate water reducer to the cement paste, continue stirring, then add stone powder, stir and mix to obtain cement mortar.

[0118] (3) adding steel fibers into cement mortar and continuing to stir, and then pouring and molding after the stirring is completed to obtain stone-like active powder concrete.

[0119] Embodiment 14

[0120] A stone-like active powder concrete:

[0121] The imitation stone active powder concrete is composed of the following raw materials in parts by mass: 1015kg cement, 280kg silica fume, 105kg mineral powder, 280kg water, 12kg polycarboxylate water reducer, 234kg steel fiber and 1167kg stone powder.

[0122] The preparation method is the same as Example 1.

[0123] Embodiment 15

[0124] A stone-like active powder concrete:

[0125] The imitation stone active powder concrete is composed of the following raw materials in parts by mass: 910 kg of cement, 280 kg of silica fume, 210 kg of mineral powder, 280 kg of water, 13 kg of polycarboxylate water reducer, 234 kg of steel fiber and 1167 kg of stone powder.

[0126] The preparation method is the same as Example 1.

[0127] Comparative Example 1

[0128] A stone-like active powder concrete:

[0129] On the basis of Example 1, the mineral powder is replaced with fly ash, and the imitation stone active powder concrete is composed of the following raw materials in parts by mass: the following raw materials in parts by mass: 1015kg cement, 280kg silica fume, 105kg fly ash, 252kg water, 8kg polycarboxylate water reducer, 234kg steel fiber and 1167kg stone powder.

[0130] The preparation method is the same as Example 1.

[0131] Comparative Example 2

[0132] On the basis of Example 9, 210 kg of mineral powder was replaced with 210 kg of fly ash, and the imitation stone active powder concrete was composed of the following raw materials in parts by mass: 910 kg of cement, 280 kg of silica fume, 210 kg of fly ash, 252 kg of water, 8 kg of polycarboxylate water reducer, 234 kg of steel fiber and 1167 kg of stone powder.

[0133] The preparation method is the same as Example 1.

[0134] Comparative Example 3

[0135] On the basis of Example 1, the stone powder particle size distribution was changed to prepare the imitation stone active powder concrete, which was composed of the following raw materials in parts by mass: 1015 kg cement, 280 kg silica fume, 105 kg mineral powder, 252 kg water, 8 kg polycarboxylate water reducer, 234 kg steel fiber and 1167 kg stone powder.

[0136] The particle size gradation of stone powder is:

[0137] 1.18mm≤particle size<4.75mm accounts for 40wt.%;

[0138] The proportion of particles with a diameter of 0.3 mm or less and a diameter of 1.18 mm is 30 wt.%;

[0139] The proportion of particles with a diameter of 0.075 mm or less and less than 0.3 mm is 25 wt.%;

[0140] The proportion of particles with a diameter of less than 0.075 mm is 5 wt.%.

[0141] The preparation method is the same as Example 1.

[0142] Comparative Example 4

[0143] On the basis of Example 1, 1167 kg of stone powder was replaced with 1167 kg of quartz sand, and the imitation stone active powder concrete was composed of the following raw materials in parts by mass: 1015 kg of cement, 280 kg of silica fume, 105 kg of mineral powder, 252 kg of water, 8 kg of polycarboxylate water reducer, 234 kg of steel fiber and 1167 kg of quartz sand.

[0144] Table 1 Amount of raw materials (kg)

[0145]

[0146]

[0147] According to GB 50164-2011, GB / T 50080-2011, GB / T 50082-2009 and GB / T 50081-2019, the strength of the stone-like reactive powder concrete prepared in Examples 1 to 15 and Comparative Examples 1 to 4 was tested, wherein the strength test included 3-day, 7-day, and 28-day compressive strength, 28-day splitting tensile strength, and 28-day flexural strength tests, and the test results are shown in Tables 2 and 3.

[0148] Table 2 Compressive strength of concrete

[0149]

[0150]

[0151] It can be seen from Examples 1 and 9 and Comparative Examples 1 and 2 that the compressive strength of concrete using fly ash as a cementitious material is lower than that of concrete using mineral powder. It can be seen from Example 1 and Comparative Example 3 that changing the particle size distribution of stone powder will reduce the compressive strength of stone-like active powder concrete. Comparing Comparative Example 4 with Example 1, it is found that the strength of stone-like active powder concrete prepared using quartz sand is only 5.96MPa higher than that of concrete prepared using stone powder. However, the market price of quartz sand is about 600 yuan per ton, while the price of stone powder is 50 to 100 yuan per ton. Therefore, it is more economical to use stone powder, which is cheaper than quartz sand, to prepare stone-like active powder concrete.

[0152] It can be seen from Examples 1, 3, 6, 11 and 14 that the strength of the stone-like reactive powder concrete increases first and then decreases as the water-binder ratio increases. It can be seen from Examples 2, 3, 4, 5, 6, and 7 that when the water-binder ratio is as low as 0.16 and 0.17, due to the high activity of cement and silica fume, after the addition of mineral powder, the amount of cement is reduced in disguise, resulting in a decrease in its hydration reaction products, so that after the addition of mineral powder, its 28d compressive strength will be slightly lower than that of the stone-like active powder concrete without mineral powder. It can be seen from Examples 8, 1, 9, 10, 11, and 12 that due to the increase in the water-binder ratio, part of the mineral powder exerts its volcanic ash effect, generates hydrated calcium silicate gel with calcium hydroxide, fills the voids inside the concrete, makes the concrete more compact, and the micro-aggregate effect of the mineral powder itself also fills the voids inside the concrete very well, thereby improving the strength of the stone-like active powder concrete. However, when 15% of the mineral powder is added, the excessive reduction in the amount of cement reduces the active effect and hydration products in the concrete, the calcium hydroxide content is low, and the amount of mineral powder added is too much, resulting in an increase in the water-cement ratio of the concrete and a decrease in the mechanical properties of the concrete.

[0153] The 3d imitation stone active powder concrete with the highest compressive strength is Example 5, which is 98.44 MPa, and the 7d imitation stone active powder concrete with the highest compressive strength is also Example 5, which is 106.40 MPa. The 28d imitation stone active powder concrete with the highest compressive strength is Example 1, which is 132.58 MPa.

[0154] The 3d compressive strength of the stone-like active powder concrete prepared in Examples 1, 5, 6, 8 to 15 can reach more than 70% of the 28d compressive strength; the 7d compressive strength of the stone-like active powder concrete prepared in Examples 1 to 15 can reach more than 75% of the 28d compressive strength.

[0155] Table 3 Splitting tensile strength and flexural strength of concrete

[0156]

[0157]

[0158] The splitting tensile strength of ordinary concrete is 3.25MPa-4.58MPa, and the flexural strength is 4.5MPa-10MPa. As can be seen from Table 3, the splitting tensile strength and flexural strength of the stone-like active powder concrete prepared by the present invention are much higher than those of ordinary concrete. As can be seen from Examples 1, 3, 6, 11, and 14, the splitting tensile strength of the 28d stone-like active powder concrete increases first, then decreases, and then increases again as the water-binder ratio increases. The maximum splitting tensile strength of the 28d stone-like concrete is Example 8, which has a strength of 17.55MPa.

[0159] It can be seen from Examples 1 and 9 and Comparative Examples 1 and 2 that the splitting tensile strength and flexural strength of the active powder concrete using fly ash are lower than those of the stone-like active powder concrete prepared using mineral powder; it can be seen from Example 1 and Comparative Example 3 that changing the particle size gradation of stone powder will reduce the splitting tensile strength and flexural strength of the stone-like active powder concrete; by comparing Comparative Example 4 with Example 1, it is found that although the splitting tensile strength and flexural strength of the stone-like active powder concrete prepared using quartz sand are improved to a certain extent, they are not high, and the price of quartz sand is many times more expensive than that of stone powder, so it is more economical to use stone powder to prepare stone-like active powder concrete.

[0160] The maximum flexural strength of 28d stone-like active powder concrete is Example 15, which is 25.47MPa. Without the addition of mineral powder, it can be seen from Examples 2, 5, 8, 10, and 13 that the flexural strength of 28d stone-like active powder concrete increases first, then decreases, and then increases with the increase of water-binder ratio, and its maximum flexural strength is when the water-binder ratio is 0.18; it can be seen from Examples 1, 3, 6, 11, and 14 that when mineral powder is added, its flexural strength first decreases and then increases with the increase of water-binder ratio, and its minimum flexural strength is when the water-binder ratio is 0.18, and the maximum is when the water-binder ratio is 0.2.

[0161] The stone-like active powder concrete of the present invention is not only high in strength, but also an early-strength concrete, which can reduce the construction period, save the extra costs caused by transportation and storage, and is suitable for emergency situations or projects that need to quickly reach a certain strength. The present invention uses stone powder of different particle sizes instead of quartz sand as the aggregate of the stone-like active powder concrete, which has great economic and environmental benefits. Research on the influence of stone powder characteristics on concrete performance can solve the key technical problems existing in the application of active powder concrete, and provide technical support for the promotion and application of active powder concrete; it can promote the promotion and application of active powder concrete throughout the country and solve the sand source problem in areas lacking natural sand resources.

[0162] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A stone-like active powder concrete, characterized in that: The raw materials include the following parts by weight: 910-1015 parts of cement, 280 parts of silica fume, 105-210 parts of mineral powder, 238-266 parts of water, 7-11 parts of water reducing agent, 234 parts of steel fiber and 1167 parts of stone powder; The water-to-binder ratio of the stone-like active powder concrete is 0.17-0.

19.

2. The stone-like active powder concrete according to claim 1, characterized in that: The particle size gradation of the stone powder is as follows: 1.18mm≤particle size<4.75mm accounts for 30wt.%; The proportion of particles with a diameter of 0.3 mm or less and a diameter of 1.18 mm is 45 wt.%; The proportion of particles with a diameter of 0.075 mm or less and less than 0.3 mm is 15 wt.%; The proportion of particles with a diameter of less than 0.075 mm is 10 wt.%.

3. The stone-like active powder concrete according to claim 1, characterized in that: The mineral powder is S95 grade mineral powder, with a specific surface area of ​​≥400kg / m 2 , 7d activity index>75%, 28d activity index>95%, particle size is 0.045mm.

4. The stone-like active powder concrete according to claim 1, characterized in that: The cement is P.Ⅱ52.5 cement, with a specific surface area of ​​≥300kg / m 2 , loss on ignition ≤3.5%, particle size 0.04mm; And / or, the silica fume has a silicon dioxide content of >90%, a loss on ignition of <2%, and a particle size of 0.15 μm; And / or, the steel fiber is a copper-plated steel fiber with a diameter of 0.2 mm, a length of 12 mm, and a tensile strength of ≥2400 MPa; And / or, the water reducing agent has a water reducing rate of ≥25%, an air content of ≤6.0%, and a chloride ion content of ≤0.1%.

5. A method for preparing the stone-like active powder concrete according to any one of claims 1 to 4, characterized in that: The following steps are involved: After cement, silica fume and mineral powder are evenly mixed, water, water reducing agent, stone powder and steel fiber are added in sequence and mixed evenly, and cast into shape to obtain the imitation stone active powder concrete.

6. Use of the stone-like active powder concrete according to any one of claims 1 to 4 in the preparation of bridge piers.